Hepatitis C Virus-Induced ROS/JNK Signaling Pathway Activates the E3 Ubiquitin Ligase Itch to Promote the Release of HCV Particles via Polyubiquitylation of VPS4A - Deng, Lin; Liang, Yujiao; Ariffianto, Adi; Matsui, Chieko; Abe, Takayuki; Muramatsu, Masamichi; Wakita, Takaji; Maki, Masatoshi; Shibata, Hideki; Shoji, Ikuo (American Society for Microbiology, 2022)
We previously reported that hepatitis C virus (HCV) infection activates the reactive oxygen species (ROS)/c-Jun N-terminal kinase (JNK) signaling pathway. However, the roles of ROS/JNK activation in the HCV life cycle remain unclear. We sought to identify a novel role of the ROS/JNK signaling pathway in the HCV life cycle. Immunoblot analysis revealed that HCV-induced ROS/JNK activation promoted phosphorylation of Itch, a HECT-type E3 ubiquitin ligase, leading to activation of Itch. The small interfering RNA (siRNA) knockdown of Itch significantly reduced the extracellular HCV infectivity titers, HCV RNA, and HCV core protein without affecting intracellular HCV infectivity titers, HCV RNA, and HCV proteins, suggesting that Itch is involved in the release of HCV particles. HCV-mediated JNK/Itch activation specifically promoted polyubiquitylation of an AAA-type ATPase, VPS4A, but not VPS4B, required to form multivesicular bodies. Site-directed mutagenesis revealed that two lysine residues (K23 and K121) on VPS4A were important for VPS4A polyubiquitylation. The siRNA knockdown of VPS4A, but not VPS4B, significantly reduced extracellular HCV infectivity titers. Coimmunoprecipitation analysis revealed that HCV infection specifically enhanced the interaction between CHMP1B, a subunit of endosomal sorting complexes required for transport (ESCRT)-III complex, and VPS4A, but not VPS4B, whereas VPS4A K23R/K121R greatly reduced the interaction with CHMP1B. HCV infection significantly increased ATPase activity of VPS4A, but not VPS4A K23R/K121R or VPS4B, suggesting that HCV-mediated polyubiquitylation of VPS4A contributes to activation of VPS4A. Taken together, we propose that the HCV-induced ROS/JNK/Itch signaling pathway promotes VPS4A polyubiquitylation, leading to enhanced VPS4ACHMP1B interaction and promotion of VPS4A ATPase activity, thereby promoting the release of HCV particles.